2020
DOI: 10.1016/j.arthro.2020.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Presoaking of Semitendinosus Graft With Vancomycin Does Not Alter Its Biomechanical Properties: A Biomechanical In Vitro–Controlled Study Using Graft From Living Donors

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Our initial elution in vitro studies of vancomycin from bovine tendons suggested a 5 mg/mL soak solution for 15 minutes would achieve adequate levels of vancomycin to decontaminate the graft while not being at risk of causing secondary tissue damage due to prolong elution. 4 Subsequent time zero studies have confirmed that 5 mg/mL is an appropriate concentration [5][6][7][8] to avoid injury to tenocytes chondrocytes and not alter the grafts material properties. Our initial and subsequent observational clinical series was supportive of our "colonized graft-infected joint" hypothesis, finding no infections when using the "vancomycin wrap" compared with a historical cohort with either similar or reduced rates of graft failure.…”
Section: See Related Article On Page 1683mentioning
confidence: 99%
“…Our initial elution in vitro studies of vancomycin from bovine tendons suggested a 5 mg/mL soak solution for 15 minutes would achieve adequate levels of vancomycin to decontaminate the graft while not being at risk of causing secondary tissue damage due to prolong elution. 4 Subsequent time zero studies have confirmed that 5 mg/mL is an appropriate concentration [5][6][7][8] to avoid injury to tenocytes chondrocytes and not alter the grafts material properties. Our initial and subsequent observational clinical series was supportive of our "colonized graft-infected joint" hypothesis, finding no infections when using the "vancomycin wrap" compared with a historical cohort with either similar or reduced rates of graft failure.…”
Section: See Related Article On Page 1683mentioning
confidence: 99%
“…Mechanical testing determined the stress-strain curve, Young's modulus, ultimate tensile stress, ultimate tensile elongation (UTE) before failure and elastic limit. No significant difference was observed between the 2 groups for all investigated parameters 16 .…”
Section: Experimental Studiesmentioning
confidence: 70%
“…Data has not reported any adverse effects, such as graft degeneration, increased laxity, or a change in functional outcome at short-to medium-term follow-up 16,30,31 . Experience from spinal surgery has not shown any negative consequences from vancomycin use 17,32 .…”
Section: Lack Of Toxicitymentioning
confidence: 99%
“…After soaking, the tendons showed no signs of biomechanical impairment. Similarly, Jacquet et al [13] in a study using living donors found that presoaking of human semitendinosus grafts with vancomycin (5 mg/mL) in a solution does not alter their biomechanical properties at time zero compared with a control group presoaked in saline solution.…”
Section: Discussionmentioning
confidence: 92%